ANALISIS PROFITABILITAS, STRUKTUR MODAL DAN NILAI TUKAR TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERTAMBANGAN - Tiara Putri Utami (2022)
This research is a quantitative study that aims to determine and analyze the effect of liquidity, profitability, and solvability on stock prices in mining sector companies listed on the Indonesia Stock Exchange in 2017-2021. This study used 20 companies as samples with purposive sampling method. Data analysis was performed using Microsoft Excel 2019 and hypothesis testing in this study used Panel Data Regression Analysis with the E-Views 12. The results of the study partially show that, (1) profitability has a significant effect on mining stock prices, (2) capital structure has a significant effect on mining stock prices, (3) the exchange rate doesn't have a significant effect on mining stock prices.